2013
DOI: 10.1063/1.4801800
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic simulations of shock-induced microjet from a grooved aluminium surface

Abstract: Molecular dynamics simulations have been used to study the microjet from a grooved aluminium surface under shock loading. Plastic deformation and release melting during microjetting are both presented by the centrosymmetry parameter, where the effect of release melting is discussed in detail. Consequently, we obtain the change law of microjet morphology and mass with the shock strength. The microjet mass is found to keep a linear increase with the post-shock particle velocity prior to release melting, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…Distinct defects may generate thin jets (which is sometimes referred to as microjetting) while a global roughness can lead to the expansion of a cloud of fine particles (sometimes called material ejection). Because this cloud may disrupt surface diagnostics used in shock physics (velocity interferometry, pyrometry, reflectivity) and because the impact of the ejecta can cause severe damage to nearby equipment in practical, engineering applications, this process has been widely studied both theoretically and experimentally under impact or explosive loading [1][2][3][4][5][6][7][8][9][10][11][12][13]. In a recent paper, we used laser driven shock loading to investigate microjetting from triangular, individual grooves of micrometric dimensions in several metals, both below and above shockinduced melting [14].…”
Section: Introductionmentioning
confidence: 99%
“…Distinct defects may generate thin jets (which is sometimes referred to as microjetting) while a global roughness can lead to the expansion of a cloud of fine particles (sometimes called material ejection). Because this cloud may disrupt surface diagnostics used in shock physics (velocity interferometry, pyrometry, reflectivity) and because the impact of the ejecta can cause severe damage to nearby equipment in practical, engineering applications, this process has been widely studied both theoretically and experimentally under impact or explosive loading [1][2][3][4][5][6][7][8][9][10][11][12][13]. In a recent paper, we used laser driven shock loading to investigate microjetting from triangular, individual grooves of micrometric dimensions in several metals, both below and above shockinduced melting [14].…”
Section: Introductionmentioning
confidence: 99%
“…Observed from the inset of Fig. 4, the total amount of ejected particles could be estimated with higher accuracy, compared to the previous simulation 18 and experiment. 6 These three configurations displayed in the inset of Fig.…”
Section: B Microjetting Factormentioning
confidence: 62%
“…Germann et al 16 carried out a large-scale MD study of RMI development by impinging upon a Cu/vacuum or Cu/Ne interface and observed the jet breakup and droplet formation on long enough timescales. Shao et al 18 investigated the effect of release melting on microjetting at a grooved Al surface and exhibited a linear relation between micro-jet mass and shock velocity. Durand and Soulard 19 showed a generic ejecta size distribution with a combination of a power law scaling and exponential form for the melted metals.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23] Some MD simulations were also performed within the context of Richtmyer-Meshkov instability. [24][25][26][27][28][29] MD simulations provide unique insights into jetting process at finest spatial and temporal scales often not accessible by experiments.…”
Section: Used In-linementioning
confidence: 99%
“…Recently, Durand and Soulard investigated Cu jet breakup. 22 Shao et al 23 studied the release melting effect on Al microjets from wedged grooves and found that jetting mass can be enhanced by release melting, and observed a linear relation between jet mass and shock strength (particle velocity). Dimonte et al 29 on symmetrical, wedged, grooves on a single crystal surface, and systematic investigations of microstructure effects are rare.…”
Section: Used In-linementioning
confidence: 99%